The relative effectiveness of computer-based and traditional resources for education in anatomy - Khot, Zaid; Quinlan, Kaitlyn; Norman, Geoffrey R.; Wainman, Bruce (Anatomical sciences education, 2013)
There is increasing use of computer–based resources to teach anatomy, although no study has compared computer‐based learning to traditional. In this study, we examine the effectiveness of three formats of anatomy learning: (1) a virtual reality (VR) computer‐based module, (2) a static computer‐based module providing Key Views (KV), (3) a plastic model. We conducted a controlled trial in which 60 undergraduate students had ten minutes to study the names of 20 different pelvic structures. The outcome measure was a 25 item short answer test consisting of 15 nominal and 10 functional questions, based on a cadaveric pelvis. All subjects also took a brief mental rotations test (MRT) as a measure of spatial ability, used as a covariate in the analysis. Data were analyzed with repeated measures ANOVA. The group learning from the model performed significantly better than the other two groups on the nominal questions (Model 67%; KV 40%; VR 41%, Effect size 1.19 and 1.29, respectively). There was no difference between the KV and VR groups. There was no difference between the groups on the functional questions (Model 28%; KV, 23%, VR 25%). Computer‐based learning resources appear to have significant disadvantages compared to traditional specimens in learning nominal anatomy. Consistent with previous research, virtual reality shows no advantage over static presentation of key views. Anat Sci Educ 6: 211–215. © 2013 American Association of Anatomists.